Penerapan Model Kooperatif Tipe TGT Dengan Media Wordwall Untuk Meningkatkan Prestasi Belajar Siswa - Winarni, Intan Wahyu; Pamujo, Pamujo (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2026)
This study aimed to improve the science learning achievement of fifth-grade students at SD N 1 Karangnangka through the implementation of the team games tournament cooperative learning model assisted by Wordwall as a learning medium under the theme